Urinary Gamma-Glutamil Transferase as an Early Biomarker of Renal Disease in Dogs with Leishmaniosis - Patricia Ruiz; Inmaculada Sevidane; Angela Durán; Ana Belén García; Beatriz Macías-García; Rafael Barrera (Veterinary Sciences)
Canine leishmaniosis, caused by Leishmania infantum, is a zoonotic disease often leading to chronic kidney disease (CKD). Early detection of renal damage is critical for prognosis and treatment, as conventional biomarkers, such as serum creatinine and symmetric dimethylarginine (SDMA), are inadequate for detecting early stages of renal dysfunction. This study evaluates the urinary gamma-glutamyl transferase-to-creatinine ratio (uGGT/c) as an early biomarker for renal injury in dogs with leishmaniosis, including 17 healthy dogs and 77 dogs with leishmaniosis, categorized using the International Renal Interest Society (IRIS) guidelines. Plasma and urinary parameters, including uGGT/c, were analyzed. Elevated uGGT/c ratios were observed in over 50% of non-azotemic and non-proteinuric dogs and all dogs with mild-to-moderate proteinuria. The uGGT/c ratio demonstrated a 90.4% sensitivity and 80% specificity for early detection of renal tubular damage, outperforming plasma creatinine (44.2%) and SDMA (51.9%). The uGGT/c ratio correlated strongly with proteinuria (UPC; r = 0.716, p < 0.001) and SDMA (r = 0.591, p < 0.001), indicating its usefulness as an early indicator of renal dysfunction. Despite the small sample size, the implementation of the uGGT/c ratio as promising biomarker could improve early diagnosis and clinical intervention, helping to avoid irreversible renal damage in dogs affected by leishmaniosis.